Impact of atrial fibrillation detected by extended monitoring—A population‐based cohort study. Issue 6 (25th April 2017) - Busch, Mathias C.; Gross, Stefan; Alte, Dietrich; Kors, Jan A.; Völzke, Henry; Ittermann, Till; Werner, André; Krüger, Anne; Busch, Raila; Dörr, Marcus; Felix, Stephan B.
Abstract : Background: The clinical relevance of extended monitoring of AF in the general population is unclear. The study evaluated the detection of AF using transtelephonic electrocardiography and the clinical relevance of additional AF findings, especially with regard to stroke risk and mortality. Methods: The data of 1678 volunteers participating in the tele‐ECG‐subproject of the Study of Health in Pomerania was evaluated. Occurrence of AF as revealed by tele‐ECG and conventional ECG was evaluated. Associations with mortality, history of stroke, and other clinical parameters were analyzed. Results: AF was detected in 21 subjects (1.3%) by conventional ECG (ECG‐AF) and in 43 (2.6%) by tele‐ECG. All individuals with AF revealed by conventional ECG were also diagnosed to have AF by tele‐ECG; 22 were diagnosed by tele‐ECG only (Tele‐AF). During follow‐up (median: 6.3 years) 42/1635, 1/22, and 5/21 participants died in the no‐AF‐, tele‐AF‐, and ECG‐AF groups ( p  < .001). Whereas, in comparison to the no‐AF group, the risk of death was higher in the ECG‐AF group (HR 9.4; 3.7–23.8; p  < .001), there was no significant increase in mortality in the tele‐AF group (HR 1.9; 0.26–14.0; p  = .52). Prevalence of stroke history was higher in the ECG‐AF group (19%; 5.5–42%) than with the no‐AF (1.9%; 1.3–2.7%; p  = .001) and the tele‐AF groups (0%; 0–15%; p  = .05). Conclusions: Tele‐ECG identifies significantly more AF cases in a population‐based setting compared to conventional ECG. The impact of AF diagnosed only by extended monitoring differs from conventionally diagnosed AF. Additional studies are warranted, since this might have an impact on clinical management.